Corippus' Triumphal Ethnography: another look at Iohannis II.28–161. (29th April 2019) - Merrills, Andy
Abstract: The so-called 'catalogue of tribes' in Corippus, Iohannis, II.28–161 is central to the historical ethnography of Moorish North Africa in Late Antiquity, yet the sources behind this passage and its poetic function have never been directly addressed. The present paper argues that Corippus derived this material from the trophies carried in the triumphal procession that marked the successful conclusion of John Troglita's campaigns in 548. The evocation of this ceremony at the outset of Corippus' narrative corresponds to the ironic tone which permeates the work, but also explains the eccentric form of the material included within the catalogue. The paper concludes with some observations about the implications of this for modern understanding of Moorish 'tribal' society in the later Roman and early Byzantine period. Abstract : يمثل ما يسمى "فهرس القبائل " في ملحمة يوهانيس II.28–161 لكوريبوس (Corippus' Iohannis) جزءاً رئيسياً في الإثنوغرافيا التاريخية لمغاربة شمال أفريقيا في العصر القديم المتأخر (Late Antiquity)، ومع ذلك فإن مصادر هذه القطعة و وظائفها الشعرية لم يتم التطرق لهما مسبقاً بشكل مباشر . تبحث هذه الورقة في أن كوريبوس استمد هذه المادة من الجوائز التي حملت في 'موكب النصر ' الذي اختتمت به الحملات العسكرية الناجحة لجون تروجليتا في سنة 548 ميلادي . إن استحضار كوريبوس لهذا الحفل في بداية سرده، يتوافق مع النغمة الساخرة التي تخللت العمل، و يفسر أيضاً الشكل الغريب للعناصر المدرجة في الفهرس . وتختتم الورقة ببعض الملاحظات حول الآثار المترتبة من هذا على الفهم الحديث لمجتمع "القبائل " المغاربي في العصر الروماني والفترة البيزنطية المبكرة .